Data independent acquisition reveals in-depth serum proteome changes in uremic pruritus - Wen-Jing, Zhao; Rui-Zhi, Tan; Si-Yuan, He; Xiao-Mei, Du; Qiong-Dan, Hu; Xiao-Qian, Zhang; Wen-Hua, Huang; Hong-Wei, Su; Jian, Liu; Qiong, Zhang; Li, Wang (Frontiers in Physiology, 2024)
Uremic pruritus (UP) is one of the common symptoms in patients with uremia, and its etiology and mechanism have not been fully understood. In view of the high incidence of UP, finding the specific changed proteins in blood of UP patients will help revealing the potential biological mechanisms of UP and explore biomarkers. In this study, LC-MS/MS based data independent acquisition (DIA) mode was used to analyze the serum samples of 54 UP patients (DKD-UP, HN-UP and GN-UP, n=18 for each), 18 uremic patients without pruritus (Negative) and 18 CKD patients without pruritus (CKD). In DIA mode, a total of 7075 peptides and 959 proteins were quantified, among which, there are 4 upregulated and 13 downregulated DEPs in DKD-UP VS Neg, 5 upregulated and 22 downregulated DEPs in HN-UP VS Neg, and 3 upregulated and 23 downregulated DEPs in GN-UP VS Neg, respectively. The DEPs of these three comparison groups were intersected to obtain a common DEPs, COMP. Subsequently, a total of 67 common DEPs were identified in the three UP groups compared with the CKD group, of which 40 DEPs were upregulated and 27 DEPs were downregulated. After GO, KEGG, and PPI analysis, we found that the DEPs between UP and CKD mainly involved mitochondrial function (MT-CYB, PRDX2, TOMM22), inflammation (CD59, CSF1), renal injury (WFDC2), and neural function (CAP1, VGF). Our data raises a potential molecular understanding of the pathogenesis of UP and provides new evidence for the identification of these DEPs as possible biomarkers for UP.